2002
DOI: 10.1381/096089202321144621
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Motility and Reflux Symptoms Before and After Bariatric Surgery

Abstract: The present results do not show any effect of gastric reduction surgery on postoperative esophageal function or gastroesophageal reflux symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 17 publications
4
67
0
2
Order By: Relevance
“…It has become apparent that esophageal dilatation is not as prevalent in this patient population as previously reported [24]. In addition, a recent report reveals a low incidence of primary esophageal motility disorders (2%) in morbidly obese patients [16], strengthening the argument that it is not a necessary routine preoperative test.…”
Section: Discussionmentioning
confidence: 55%
“…It has become apparent that esophageal dilatation is not as prevalent in this patient population as previously reported [24]. In addition, a recent report reveals a low incidence of primary esophageal motility disorders (2%) in morbidly obese patients [16], strengthening the argument that it is not a necessary routine preoperative test.…”
Section: Discussionmentioning
confidence: 55%
“…These varied results of weight loss on GERD symptoms could be because of small sample size, gender differences, wide variation in BMI of subjects (23 vs. 43), and use of different weight loss methods (various lifestyle changes vs. surgical approaches) (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Furthermore, a number of lifestyle intervention treatments have been attempted for GERD-low calorie diet, use of fruits/ vegetables, and physical activity; individually each intervention has no direct correlation with GERD improvement as shown in previous population-based studies (13,22,23) and a recent meta-analysis (32).…”
Section: Discussionmentioning
confidence: 99%
“…Previous data on the impact of weight loss achieved through various lifestyle (dietary changes and physical activity) (21)(22)(23)(24)(25) or surgical methods (Roux-en-Y gastric bypass or vertical band gastroplasty) (26)(27)(28)(29)(30) on GERD symptoms are scarce and with conflicting results (31). A systematic review evaluating the effects of various life style changes on GERD symptoms suggested that weight loss and head of bed elevation could improve symptoms of GERD (32).…”
Section: Introductionmentioning
confidence: 99%
“…In only six of 814 patients (0.9%), as reported by Ghassemian et al, X-ray examination of the GI tract demonstrated relevant abnormality, and not a single operation had to be delayed due to the results of the GI tract series (EL 4 [122]). Using esophageal manometry, two recent case series found abnormalities in only 13 to 20% of patients and being without clinical consequences (EL 4 [169,186]). Jaffin et al, however, described that esophageal disorders were highly prevalent (61%) and associated with postoperative results (EL 4 [150]).…”
Section: Preoperative Diagnosticsmentioning
confidence: 99%